Deploying Citrix MetaFrame presentation server 3.0 with Windows server 2003 terminal services - Wilson, Connie S. (Syngress Pub., 2004)
Almost 100% of all Fortune 500 and Fortune 1000 companies use Citrix. This book covers the new release to Citrix MetaFrame and how companies can deploy it in their disaster recovery plans. Server Based Computing has been established as a solid networking model for any size business. Why? Because it guarantees cost savings, fast deployment, scalability, performance, security and fast recoverability. Think "mainframe," but updated, pretty, shiny, and effective! Server based computing is the mainframe with a vengeance. Terminal Server and Citrix MetaFrame offer the advantages of the old mainframe coupled with the benefits, gadgets, and appeal of the personal computer. * Manage applications from a central location and access them from anywhere * Build scalable, flexible, and secure access solutions that reduce computing costs and increase the utility of your network * The first book that covers Citrix MetaFrame Presentation Server 3.0 and Windows Server 2003 Terminal Services.